Investigate The Impact Of Ai In Diagnostic Radiology, Exploring Its Use In Detecting Conditions Like Cancer, Fractures, Or Neurological Disorders (Journal of Pharmaceutical Negative Results, 2022)
Background: This paper aims to argue that artificial intelligence (AI) has revolutionized diagnostic radiology by enhancing the effectiveness and efficiency of the diagnostics. The incorporation of AI algorithms in the diagnosis of radiology findings has a special informative impact when it comes to explaining diseases like cancer, fractures, neurological disorders. Patterned recognition and anomaly detection in an AI helps a radiologist in making accurate diagnoses.Objectives: To measure the performance of AI in increasing diagnostic accuracy with regards to cancer, fracture and neurological disorder and to know the usefulness comparing with the use of conventional diagnosis methods.Study Design: This study was designed as a comparative diagnostic accuracy study.Place and Duration of Study: Department Of Radiology Watim Medical College, Rawalpindi form jan 2022 to March 2022Methods: A pilot research involved 100 participants with AI-based diagnostic tools applied to the images from X-ray, MRI, and CT scans. The outcomes of the radiologists were then checked against the AI diagnosis results. , it is important to note that some of the main outcomes reported were detection accuracy, sensitivity and specificity. Power Point presentations made by the authors include comparisons of AI’s performance to human radiologists, in which normal deviate statistics, standard deviations, and p-values were used to determine the significance level.Results: AIs enhanced diagnostic ability was evaluated to have 95% accuracy in cancer diagnosis and 1.2 in fracture diagnosis, values that were only slightly deviant of the standard standard deviation of 0.8. For cancer signals, the p-value was <0.05 suggesting better efficacy than the conventional detection techniques. Sensitivity for neurological disorder detection was fair at 89% and the p-value of 0.03.Conclusions: AI reveals desirable preparedness in enhancing diagnostic accuracy of numerous ailments. Furthermore, improvement and policy adjustments are needed for wider implementation although it improves the diagnostic chances for radiologists. AI will likely expand its role as an instrument providing new opportunities for faster and more accurate diagnostics.